DEVELOPMENT OF THE SOWING SYSTEM OF THE SOWING COMPLEX FORINTERNAL-SOIL DIFFERENTIATED MINERAL FERTILIZER WITH SIMULTANEOUS SOWING OF CEREAL - RUTKEVYCH, VOLODYMYR; OSTAPENKO, VALERIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The issue of increasing the effectiveness of post-sowing intra-soil differentiated application of the main and starting dose of granular mineral fertilizers in the system of precision agriculture is considered. The need to use differential application of granular mineral fertilizer and machines that ensure high-quality performance of this technological process, taking into account the heterogeneity of the content of nutrients in the soil in certain areas of the field, is indicated. It is also indicated the need to develop and introduce into production highly accurate automated information technologies based on the use of high-performance means of mechanization. The indicated shortcomings of modern seeding machines: lack of adaptability for simultaneous differentiated introduction of the main and starting dose, as a result of which they lack highly adapted dispensers, appropriate control and management systems. The construction and technological scheme of the seeding complex is proposed and the pneumatic seeding system of this unit is developed for post-sowing intra-soil differentiated application of the main and starting dose of granular mineral fertilizers in the precision farming system. The proposed seeding complex will make it possible to eliminate the excessive application of mineral fertilizers, which can cause an increase in the activation of microbiological processes in the soil and have negative ecological consequences, leading to the deterioration of the physic-chemical and biological properties of the soil. The use of resource-saving technologies of precision agriculture in the agro-industrial complex of Ukraine will allow to ensure the management of production processes at the expense of information technologies, robotic and automated systems, which will allow to bring domestic agricultural enterprises to a new level.